Objective Approach in Supplier Selection: Integration of RECA Weighting and Combinative Distance-based Assessment Method - Setiawansyah Setiawansyah; Iryanto Chandra (PT. Tech Cart Press, 2026)
Supplier selection is a strategic decision that directly affects operational efficiency and supply chain performance. This study aims to propose a multi-criteria decision-making approach to evaluate and rank suppliers objectively based on multiple performance indicators. The evaluation is conducted using five main criteria, namely price, quality, delivery, responsiveness, and capacity and flexibility. A total of nine supplier alternatives were assessed, and a quantitative decision model was applied to aggregate the performance of each alternative into a final score and ranking. The results indicate that the proposed approach is capable of clearly distinguishing supplier performance, as reflected in the significant differences in final scores across alternatives. The ranking results show that PT Cipta Solusi Persada achieved the first position with a final score of 0.5171, followed by PT Karya Nusantara with a score of 0.4626 in the second position, and PT Prima Logistik Indonesia with a score of 0.3922 in the third position. These findings demonstrate that suppliers with balanced performance across all criteria tend to achieve higher rankings. The study also highlights that suppliers with lower rankings generally exhibit structural weaknesses in key criteria, suggesting the need for performance improvement or strategic reconsideration.